Master Teachers and Department Heads as Science Instructional Leaders: A Case Study on Their Role as Instructional Programme Managers - Magnaye, Louiesito Jr. (SEAQIS Journal of Science Education, 2023)
As instructional leaders, master teachers and department heads are equally important in harnessing commendable scholastic performance for both teachers and students. This paper explored the case on how science master teachers and department heads practice on science instructional leadership, thereby creating an in-depth description and analysis of their ideals and realities. An electronic open-ended survey questionnaire and semi-structured individual interviews with six participants were used to collect data. Findings revealed that the practices of master teachers and department heads on coordinating the science curriculum dimension include fostering professional development among science teachers, providing technical assistance to science teachers, and organizing programs, projects and activities related to science. Meanwhile, ensuring instructional competence of science teachers and performing classroom observation as prescribed by Department of Education are their practices under supervising and evaluating science instructions. For monitoring student’s progress, participants’ practices include focusing diverse assessment strategies towards science process skills. This study also unveiled that the participants faced dilemma in their role as instructional leaders because of additional tasks aside from the prescribed duties and responsibilities of science master teachers and department heads expected from them. Moreover, documentary analysis disclosed that the instructional leadership of science master teachers and department heads significantly influence the school performance. Further study on the relationship between instructional competence of school leaders to its performance indicators is warranted.